The Application of Blended Learning Using Edmodo Media to Increase Learning Motivation and Achievement in Learning Physics - Kusumawati, Yulya; Umar, Umar; Hakim, Lukmanul (Empiricism Journal, 2022)
The technology of learning in 4.0 requires students to be more active in obtaining information both at school and community. In order to engage students how to use their own effort and hard work to find knowledge as a source of learning, Indonesia has already implemented e-learning media. However, learning media is still less effective in influencing the way of learning in SMA Negeri 1 Moyo Hulu, it because of motivation and learning achievement to decrease. Therefore, research was conducted on the application of blended learning using Edmodo application to increase motivation and achievement in learning physics in first grade of SMA Negeri 1 Moyo Hulu. The purpose of this research are;  1) To analyze the factors that can increase motivation to learn physics in first grade of SMA Negeri 1 Moyo Hulu, 2) to identify the differences between  the application of blended learning using Edmodo application and conventional to increase learning motivation and achievement of SMA Negeri 1 Moyo Hulu, and 3) To analyze the effectiveness of applying blended learning using Edmodo application to increase learning motivation and achievement of SMA Negeri 1 Moyo Hulu. The researcher used quasi-experimental research with Nonequivalent control group design. The sampling technique used is cluster sampling. Data collection techniques using observation, questionnaires, tests, interviews, and documentation. Instrument test using validity test and reliability test. Furthermore, the data were analyzed using factor analysis techniques, different test analysis (paired sample t test), and effectiveness analysis. Based on the results of the research that has been done, it was found that the factors that can increase the motivation to learn physics in first grade of SMA Negeri 1 Moyo Hulu, consist of 4 factors namely; family, school environment, educators and learning media. Learning media is an important factor, where the application of Edmodo greatly influences learning motivation and achievement with an average value comparison of experimental class motivation 8,69> 5,94 control class motivation, and experimental class achievement 33,94> 27,42 control class achievement, so it can be concluded that edmodo is effective to be applied in the physics learning process at SMA Negeri 1 Moyo Hulu.